Computational biomechanics in the remodelling rat heart post myocardial infarction - Masithulela, Fulufhelo James (Division of Cardiology, 2016)
Cardiovascular diseases account for one third of all deaths worldwide, more than 33% of which are related to ischemic heart disease, including myocardial infarction (MI). This thesis seeks to provide insight and understanding of mechanisms during different stages of MI by utilizing finite element (FE) modelling. Three-dimensional biventricular rat heart geometries were developed from cardiac magnetic resonance images of a healthy heart and a heart with left ventricular (LV) infarction two weeks and four weeks after infarct induction. From these geometries, FE models were established. To represent the myocardium, a structure-based constitutive model and a rule-based myofibre distribution were developed to simulate both passive mechanics and active contraction.